PENGARUH PERENCANAAN DAN REGULASI TERHADAP ANGGARAN BERBASIS KINERJA MELALUI PENATAUSAHAAN SEBAGAI VARIABEL INTERVENING (Survei Pada Pemerintah Daerah Kabupaten Donggala) - Irawati, Irma (Katalogis, 2017)
The research aims to determine and analyze: 1) significant influence of planning on administration; 2) significan influence of regulation on administration; 3) significant influence of administration on performance-based budgeting; 4) significant influence of planning on performance-based budgeting; 5) significant influence of administration on performance-based budgeting; 6) significant influence of planning through administration on performance-based budgeting; 7) significant influence of regulation through administration on performance-based budgeting. This research applies survey method. Data use is quantitative from primary and secondary sources. Sample includes 44 governmental working units selected by proportionate stratified random sampling. Data is analyzed with patg analysis with AMOS 22.00.The results conclude that 1. Planning has positive ang significant influence on administration; 2) regulation has positive and significant influence on administration; 3) administration has positive and significant influence on performance-based budgeting; 4) planning has positive and significant influence on performance-based budgeting; 5) regulation has positive and significant influence on performance-based budgeting; 6) planning through administration has positive and significant influence on performance-based budgeting; 7) regulation through administration has positive and significant influence on performance-based budgeting.